HUBUNGAN RIWAYAT PEMBERIAN ASI DENGAN KEJADIAN PNEUMONIA PADA BALITA (Jurnal Keperawatan Indonesia Florence Nightingale, 2021)
This research was based on the high incidence of pneumonia in West Java, especially on toddlers aged 1-4 years (78.616 cases). The numbers of those cases made West Java as the largest contributor to pneumonia cases in Indonesia. The theory states that one of the risk factors for pneumonia is a history of breastfeeding, where toddlers who get exlusive breastfeeding can be more protected from pneumonia. This study aims to determine the relationship between the history of breastfeeding and the incidence of pneumonia in toddlers at the Garuda Health Center in Bandung. The research design used was analytic survey with cross sectional approach. Data collection techniques used interviews and in determining the research sample used purposive sampling method. The population in this study were toddlers aged 12-59 months who visited the MTBS Polyclinic Garuda Public Health Center with cough symptoms leading to pneumonia, with sample of 60 toddlers studied. Data analysis used Chi Square test. The result showed there was a relationship between breastfeeding and the incidence of pneumonia in toddlers with a p value of = 0.002 (α = 5%). Recommendations for health care institutions are to be able to make effective pneumonia actions, especially concerning exlusive breastfeeding and prevention of pneumonia in children. Keywords: Breastfeeding, Pneumonia, Toddler.